جهود الموالي العلمية في تفسير القرآن الكريم - إبراهيم، أحمد خليل; المولى، قحطان عدنان بكر فياض (جامعة الانبار - كلية التربية للعلوم الإنسانية, 2023)
كان الموالي في صدر الإسلام يمثلون شريحة مهمة من الصحابة والتابعين ولهم جهود علميه كبيره في خدمة دين الإسلام عموماً والقرآن الكريم خصوصاً وإيصاله لمن بعدهم إذ كان للموالي دور بارز في تفسير آيات القرآن الكريم فمنهم من كان يسأل النبي صلى الله عليه وسلم عن تفسير بعض الآيات ومنهم من قام بنقل الروايات التي تفسر القرآن الكريم ومنهم من أصبح إماماً في التفسير إذ أقبل كثير من الموالي على العلم وخاصه علم التفسير فبرز كثير من المفسرين من الموالي مثل عطاء ابن أبي رباح وطاووس ومجاهد ابن جبر وغيرهم. فحفظ الله كتابه بأهل العلم الذين كان كثير منهم من الموالي فرفعهم الله بالعلم وبالقرآن. The Mawali at the beginning of Islam represented an important segment of the companions and followers, and they had great scientific efforts in the service of the religion of Islam in general and the Holy Qur’an in particular, and its delivery to those after them, as the masters had a prominent role in interpreting the verses of the Holy Qur’an. Those who transmitted the narrations that explain the Holy Qur’an, and some of them became an imam in interpretation, as many followers turned to knowledge, especially the science of interpretation, so many commentators emerged from the followers, such as Ataa Ibn Abi Rabah, Peacock, Mujahid Ibn Jabr and others, so God preserved his book with the people of knowledge, many of whom were from The next one, so God raised them with knowledge and the Qur’an.
Keywords: الدين الإسلامي -- صحابة الرسول -- علم التفسير -- تأويل القرآن